Strategic Development of Korean Brands in the Life Science Research Tools Sector: Insights from Global Leading Brand Strategie (aSSIST Business Review, 2026)
Background/Purpose: The Korean life science research tools market remains heavily import-dependent, with global leaders from the United States, Europe, and Canada dominating key technology domains—Next-Generation Sequencing (NGS), Flow Cytometry, Chromatography, Mass Spectrometry, and Real-Time PCR (qPCR). This study examines the strategic frameworks underlying the global dominance of five leading brands and derives actionable recommendations for Korean manufacturers seeking to build globally competitive brands. Study Design/Methodology/Approach: A qualitative, case-study methodology was employed, systematically analysing five global leaders—Illumina (NGS), BD BioSciences (Flow Cytometry), Agilent Technologies (Chromatography), Thermo Fisher Scientific (Mass Spectrometry), and Roche Diagnostics (qPCR)—across six strategic dimensions: corporate history, business strategy, branding and value proposition, customer relationship management, global market entry and localisation, and sustainability/CSR. Data were collected from annual reports, market research reports, corporate websites, and industry news through January 2025. Findings: Nine common success factors were identified across all five cases: (1) continuous technological innovation and R&D investment; (2) strategic mergers and acquisitions; (3) integrated solution provision; (4) robust global distribution and localised service networks; (5) brand value built on reliability and quality; (6) close collaboration with academia and industry; (7) national-level R&D funding support; (8) successful private capital raising; and (9) proactive education and marketing. The global market for life science research tools was estimated at USD 133.6–159.6 billion in 2023, with CAGR forecasts of 7–11% through 2032. Originality/Value: This study provides the first systematic cross-case comparison of global brand strategies across all five major life science technology domains from the perspective of Korean market development, offering six strategic recommendations—technology innovation, localisation, talent and collaboration, IP protection, branding, and government-industry cooperation—with direct implications for Korean manufacturers, policymakers, and investors.
Keywords: life science research tools; brand strategy; NGS; flow cytometry; chromatography; mass spectrometry; qPCR; Korean life science industry; global market entry; technology innovation